Upaya Pencegahan Perbedaan Diagnosis Klinis Dan Diagnosis Asuransi Dengan Diberlakukan Program Jaminan Kesehatan Nasional (JKN) Dalam Pelayanan Bpjs Kesehatan Studi Di Rsud Kota Semarang - Faik Agiwahyuanto; Sudiro Sudiro; Inge Hartini (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
Percentage of clinical and insurance diagnosis differences at Semarang City Public Hospital tended to increase. If this condition remained, it would lead to upcoding (fraud). The aim of this study was to explain a process of clinical and insurance diagnosis at a hospital in the implementation of Healthcare and Social Security Agency (Health BPJS). This was a qualitative study. Main informants consisted of doctors at an emergency room, surgeons, and internists. Informants for triangulation purpose consisted of a Hospital Director, a hospital verifier, and a head of Medical Record Unit. Data were analysed using content analysis.The results of this research showed that there were any differences in clinical and insurance diagnosis at Semarang City Public Hospital. The cause of these differences was due to differences in diagnosis and medical treatment between medical service standard of doctors at the hospital and a standard of INA-CBGs. To prevent the differences of clinical and insurance diagnosis, the Semarang City Public Hospital had formed an internal verifier team of the hospital and a Clinical Micro System team. A medical committee had a role to minimise the occurrence of upcoding by multiplying kinds of Clinical Pathway as a reference for doctors in diagnosing and determining kinds of treatments for patients.The differences of clinical and insurance diagnosis must be equated to prevent the occurrence of upcoding and disadvantage of the hospital. Efforts to prevent these differences are by adding officers, training coding, making and multiplying algorithm of clinical pathway, forming a team of Clinical Micro System, and monitoring and evaluating medical services.